Acid atmospheric deposition and its effects on terrestrial ecosystems in the Netherlands : the third and final phase (1991-1995) - Heij, G.; Erisman, J. W. (Jan Willem) (Studies in environmental science ;, 1997)
The book begins with an overview of the research topics which were addressed in the three different phases of the Dutch Priority Program on Acidification (DPPA), executed between 1985 and 1994. This chapter is followed by a chapter which deals with the emissions of acidifying substances, the concentrations and the deposition to forest and nature conservation areas. Prognoses are given for the acid deposition in 2000 and 2010; the deposition in the countries surrounding the Netherlands is also mentioned. The differences in the results of the DPPA-II are analysed. The third chapter deals with the effects of exposure and load on forests. The chapter moves from small-scale to large-scale: first the effects in laboratory-scale studies are described, then the effects in the field, both at stand level and on a regional scale. In addition, the critical thresholds (critical level of concentration and critical load of deposition) are discussed. The fourth chapter covers terrestrial ecosystems (or parts thereof) as well as weakly buffered surface waters, springs and other streams. Critical levels and loads are also discussed. The most important results are given in chapter 5. In the appendices of the book, so-called umbrella theme reports on deposition, stand modelling and effects on forests are presented which describe in more detail the scientific work performed in the third phase of the DPPA. This book will be of interest to anyone involved in research related to acidification and eutrophication; i.e., not only those who perform the research in the causal chain from emissions to effects, but also policy-makers and students.